Killing women: the visual culture of gender and violence - Burfoot, Annette; Lord, Susan (Cultural studies series, 2006)
History, memory, and mediations of murder. Mapping scripts and narratives of women who kill their husbands in Canada, 1866-1954: inscribing the everyday / Sylvie Frigon -- Neither forgotten nor fully remembered: tracing an ambivalent public memory on the tenth anniversary of the Montreal Massacre / Sharon Rosenberg -- Missing: on the politics of re/presentation / Zoey (c)louard Michele -- Killing the killers: women on death row in the United States / Kathleen O'Shea -- "Dealing with the devil": Karla Homolka and the absence of feminist criticism / Belinda Morrissey. Techniques and technologies of representing violence. Pearls and gore: the spectacle of woman in life and death / Annette Burfoot -- "I am awake in the place where women die": violent death in the art of Abigail Lane and Jenny Holzer / Lisa Coulthard -- Women and murder in the televirtuality film / Jack Boozer -- "I'm in there! I'm one of the women in that picture" / Margot Leigh Butler -- Killing time: the violent imaginary of feminist media / Susan Lord. National trouble: gendered violence. Dario Argento's The bird with the crystal plumage: caging women's rage / Frank Burke -- How positively levitating! Chinese heroines of Kung fu and Wuxia pian / Suzie S.F. Young -- The madwomen in our movies: female psycho-killers in American horror cinema / Steven Jay Schneider -- Reverence, rape--and then revenge: popular Hindi cinema's "women's film" / Jyotika Virdi -- In the name of the nation: images of Palestinian and Israeli women fighters / Dorit Naaman